A central CRMP complex essential for invasion in Toxoplasma gondii - Singer, Mirko; Simon, Kathrin; Forné, Ignasi; Meissner, Markus (PLoS biology, 2023)
Apicomplexa are obligate intracellular parasites. While most species are restricted to specific hosts and cell types, Toxoplasma gondii can invade every nucleated cell derived from warm-blooded animals. This broad host range suggests that this parasite can recognize multiple host cell ligands or structures, leading to the activation of a central protein complex, which should be conserved in all apicomplexans. During invasion, the unique secretory organelles (micronemes and rhoptries) are sequentially released and several micronemal proteins have been suggested to be required for host cell recognition and invasion. However, to date, only few micronemal proteins have been demonstrated to be essential for invasion, suggesting functional redundancy that might allow such a broad host range. Cysteine Repeat Modular Proteins (CRMPs) are a family of apicomplexan-specific proteins. In T. gondii, two CRMPs are present in the genome, CRMPA (TGGT1_261080) and CRMPB (TGGT1_292020). Here, we demonstrate that both proteins form a complex that contains the additional proteins MIC15 and the thrombospondin type 1 domain-containing protein (TSP1). Disruption of this complex results in a block of rhoptry secretion and parasites being unable to invade the host cell. In conclusion, this complex is a central invasion complex conserved in all apicomplexans.